2009
DOI: 10.1186/1471-2164-10-387
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune and systemic response in honey bees to a bacterial pathogen, Paenibacillus larvae

Abstract: BackgroundThere is a major paradox in our understanding of honey bee immunity: the high population density in a bee colony implies a high rate of disease transmission among individuals, yet bees are predicted to express only two-thirds as many immunity genes as solitary insects, e.g., mosquito or fruit fly. This suggests that the immune response in bees is subdued in favor of social immunity, yet some specific immune factors are up-regulated in response to infection. To explore the response to infection more b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 32 publications
7
131
1
1
Order By: Relevance
“…The sample was clarified for 10min at 16,100 g at 4°C and the pelleted debris was discarded, while the supernatant proteins were precipitated by adding ethanol and sodium acetate as described elsewhere (Foster et al, 2003). Hemolymph was processed as described previously (Chan et al, 2006) and hemolymph and fat body proteins were prepared for mass spectrometry, isotopically labeled and analyzed on an LTQOrbitrapXL (ThermoFisher, Loughborough, Leics, UK) exactly as described before (Chan et al, 2009). The reported relative protein expression average was calculated by averaging across at least two of the three biological replicates, provided that the total number of measured peptides for that protein was not less than three.…”
Section: Proteomics: Quantitative Liquid Chromatography/mass Spectrommentioning
confidence: 99%
“…The sample was clarified for 10min at 16,100 g at 4°C and the pelleted debris was discarded, while the supernatant proteins were precipitated by adding ethanol and sodium acetate as described elsewhere (Foster et al, 2003). Hemolymph was processed as described previously (Chan et al, 2006) and hemolymph and fat body proteins were prepared for mass spectrometry, isotopically labeled and analyzed on an LTQOrbitrapXL (ThermoFisher, Loughborough, Leics, UK) exactly as described before (Chan et al, 2009). The reported relative protein expression average was calculated by averaging across at least two of the three biological replicates, provided that the total number of measured peptides for that protein was not less than three.…”
Section: Proteomics: Quantitative Liquid Chromatography/mass Spectrommentioning
confidence: 99%
“…Furthermore, Chan et al (2009) detected increased levels of prophenoloxidase (proPO) and lysozyme in the larval hemolymph, suggesting that ProPO and lysozyme play important roles, involving killing pathogens directly. Neither abaecin nor defensin was detected in honeybee hemolymph in response to P. larvae infection (Chan et al, 2009), which is in agreement with the results of our gene expression analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This weak antimicrobial activity of abaecin seems to function as a back-up for apidaecin-resistant bacteria (Casteels et al, 1993). Recently, it was reported that the response of honeybees to P. larvae is involved with another immune effector molecule, hymenoptaecin (Chan et al, 2009). The authors were only able to quantify hymenoptaecin in the hemolymph of P. larvae-infected European honeybees.…”
Section: Resultsmentioning
confidence: 99%
“…by the American foulbrood organism Paenibacillus larvae. (Chan et al, 2009;Evans, 2004). This has been identified in colonies dosed with fenoxycarb which was observed to predispose the treated hives to European foulbrood and sacbrood (a virus) (Marletto et al, 1992).…”
Section: Interactions In Beesmentioning
confidence: 99%
“…The capacity for immune function varies with age in honeybees but not in bumble bees (James and Xu, 2011). While there are no differences in encapsulation response between developmental stages (Wilson-Rich et al, 2008) honeybee larvae and pupae have the highest total haemocyte counts and lowest levels of phenoloxidase (PO) activity but high levels of catalytically inactive pro-PO (prophenoloxidase) (Laughton et al, 2011) that is proteolytically activated upon infection (Chan et al, 2009). Phenoloxidase activity increases post-emergence reaching a plateau within the first week and does not decline with age in workers despite the reported reduction in haemocyte numbers (Schmid et al, 2008).…”
Section: Supporting Publications 2012:en-340 160mentioning
confidence: 99%